Incision and drainage of perianal abscess with primary fistulotomy in case of co-existing low variety fistula - Masum, Mohammad Nazmul Hoque; Yazdani, Asif; Biswas, Md Shahnawas; Masum, Mohammad; Bhuiyan, Masfique Ahmed; Hossain, Md Nabir; Rahman, Md Atiar (Journal of Dhaka Medical College, 2020)
Background: Perianal abscess is a clinical condition frequently encountered by surgeons. Perianal abscess originates from an infection arising in the cryptoglandular epithelium lining the anal canal. Occasionally; bacteria, fecal material or foreign matter can clog an anal gland and tunnel into the tissue around the anus or rectum, where it may then collect in a cavity called an abscess. About half of perianal abscess may manifest as fistula-in-ano which increases the risk of abscess recurrence requiring repeated drainage. Treating the fistula at the same time of incision and drainage of abscess reduce chances of recurrent abscess development and therefore likelihood of repeat surgery. Primary fistulotomy in case of low variety fistula may be advantageous for perianal abscess because fistulas are more commonly traceable and can be laid open with full preservation of external anal sphincters. Methods: 216 consecutive patients (91.6% males, 8.33% females); mean age, 39 (range 18-70 years) from July, 2015 to January, 2019 with perianal abscesses were treated by incision and drainage and primary fistulotomy. 38 patients had comorbidities as diabetes mellitus, obesity (BMI>26), tuberculosis. Patients were followed up clinically for 2 months. Digital rectal examination performed to assess anal tone before, one week and one month after surgery. Results: Operative time was on average 17 minutes (15-20 minutes). Average hospital stay was 1 day and complete healing time ranged from 30-60 days. Persistent fistulas developed in four patients after surgery (1.85%). Bleeding occurred in 2 patients (1%). Many patients had transient minor incontinence in the form of flatus and loose stool incontinence but eventually resolved after two weeks. No major incontinence was found. Patient’s satisfaction of the treatment maneuver in relation to abscess recurrence and fistula occurrence was 95%. All patients remained fully continent. Operative time, hospital stay, and time for complete wound healing were the same in both groups. Conclusion: Primary fistulotomy for co-existing low variety fistula at the time of drainage of perianal abscess results in very few persistent fistulas and no added risk of fecal incontinence. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 85-89